The Effect of Work Discipline and Work Motivation on Employee Performance at PT. Mitra Rubber Industries - Trijayadi, Mochamad Luthfi; Hermana, Cecep (Peneliti.net, 2025)
This study aims to analyze the effect of work discipline and work motivation on employee performance at PT Mitra Rubber Industries. Good work discipline reflects employee compliance with company rules and procedures, while work motivation is related to internal and external encouragement that affects employee morale and productivity. The research method used is a quantitative approach with data collection through surveys to employees of PT Mitra Rubber Industries. Data analysis was carried out using statistical techniques to test the relationship between the variables studied. The results showed that both work discipline and work motivation have a positive and significant influence on employee performance. High work discipline contributes to efficiency and effectiveness in task completion, while strong work motivation increases employee dedication and productivity. Based on these findings, companies are advised to continue developing policies that support the improvement of work discipline and provide motivational stimuli, such as reward systems and career development. Thus, companies can create a more productive work environment and increase competitiveness in the manufacturing industry.